ANALISA EFEKTIFITAS PENERAPAN APLIKASI RUANG UKOM DALAM MEMPERSIAPAKAN MAHASISWA MENGHADAPI UJI KOMPETENSI NERS - Rudini, Dini; Ekawaty, Fadliyana (Program Studi Keperawatan Universitas Jambi, 2023)
The Indonesian government has implemented a quality assurance system for higher education in the health sector, including competency tests. The aim of carrying out competency tests is to achieve graduate competency standards that meet performance competency standards, however, the Indonesian Nurses Competency Test experiences a decline in the pass rate every period. The low percentage of students passing the nurse competency test should be an evaluation material for every nurse education institution in Indonesia. Many factors can influence or become obstacles in achieving passing the nurse competency test, one of which is a lack of understanding in analyzing and answering computer based competency test questions. The aim of this research is to analyze the effectiveness of Android-based learning applications as a medium for learning and practicing Nurse competency tests. The design used in this research is a pre post test one group design. The sample from this research is 60 students participating in the Jambi University Nurse Professional Education Study Program who will be prepared using the Ruang Ukom Application learning media to take part in the nurse competency test activities. This research instrument uses the average standard of the Nurse Competency Test TryOut before the Nurse Competency Test is carried out to measure student preparation in the Indonesian Nurse Competency Test. Students were given a pretest of 180 questions, then given training intervention for 20 meetings with a duration of 1 meeting for 2 hours, then a post test was carried out. After that the data was processed using the t-test data analysis technique with α=0.05. The results of the study showed that students' readiness in facing the nursing school before being given intensive guidance using the Ruang Ukom application was at a mean of 34.75 (SD=2.144) and students' readiness in facing the Nursing School after being given intensive guidance using the Ruang Ukom application was at an average of 50.65 (SD=2.44) and the use of this application was proven to be effective in increasing student readiness in facing the nursing school (p=0.000). Exam preparation before facing the nursing competency test using the right media is important for students to increase their readiness to face UKOM so that the UKOM graduation rate can increase